Distribution of Microplastics along Mai Khao Coastline, Phuket - Pensiri Akkajit; Audomlak Khongsang (Journal of Engineering and Technological Sciences, 2022)
The distribution of microplastics at Mai Khao beach, Phuket, Thailand was studied. A total of 12 samples from four sample sites with 0.5 m x 0.5 m quadrats were taken at the intertidal zone during March and July, 2020, and sorted into two size classes (>300 µm and 20 to 300 µm). The mean abundance of microplastics at Mai Khao beach ranged from 44.08 to 68.7 items kg-1 d.w. for >300 µm and from 90.6 to 106.1 items kg-1 d.w. for the 20 to 300 µm range. White (44.94%) and blue (23.60%) colors, and fiber shape (94.5%) were dominant in particle counts; and based on µFTIR analysis the dominant polymer type was polyethylene terephthalate (94.7% by number count), with considerable fractions of cotton and cellophane. The microplastic characteristics suggest anthropogenic activities as possible sources. Notably, the abundance of microplastic found in the study area was definitely higher than at other sites investigated along the west coast or Phuket. Significant differences in the abundances of the two microplastic size classes were observed (p < 0.05), indicating that the microplastics in Mai Khao beach can accumulate in the marine food chain and transfer up along the trophic levels. Therefore, urgent attention should be given to the contamination problem, with a proper management system and a public awareness campaign, to reduce the effects of microplastic on organisms and ecosystems.